PENGARUH PERILAKU KONSUMEN TERHADAP STRATEGI PROMOSI PADA MEDIA SOSIAL - Ageng Saepudin Kanda S; Devira Vianti Putri (CV. KAMPUS AKADEMIK PUBLISING, 2024)
e-commerce is a business model that allows companies or people to buy or sell goods via the internet (online). The purpose of preparing this daily is to recognize the influence of consumer decisions on purchasing objects promoted on social media. Social media has become a pillar in conveying information, social media also plays a very important role in socialization and policy programs in introducing goods or services. Social media also provides information about the potential or natural wealth that exists in Indonesia to foreign countries with the existence of Indonesian social media which is more well-known abroad. In this research we will discuss the influence of promotions on social media on consumer behavior, on the influence of promotions on social media.